Answer:
x = ±6
Step-by-step explanation:
x^2/4=9
Multiply by 4 on each side
x^2/4 *4=9*4
x^2 = 36
Take the square root of each side
sqrt(x^2) = ±sqrt(36)
x = ±6
Answer:
B and d
Step-by-step explanation:
b and d
To determine the nth term, we must create a function.
f(n) = 1st term + common difference (n - 1)
n = term you are looking for
1st term = 1st number in the sequence
common difference = the difference between two consecutive numbers in the sequence.
based on the above sequence, the 1st term is 2, its common difference is 3.
f(n) = 2 + 3(n-1)
Assuming we are looking for the 5th term
f(5) = 2 + 3(5-1)
= 2 + 3(4)
= 2 + 12
f(5) = 14 as you can see in the above sequence 14 is the 5th term.
For any other value of the nth term, simply substitute n by the number of the term and solve the equation.
Well nine times 2 is 18. and 3 times 6 is 18 so is is it 2